Protocol for handling contaminated maritime cargo returned to the country - Madison Coelho de Almeida; Patrick Rodrigues Perrotta; Raul dos Santos; Delvonei Alves de Andrade; Maria Angélica Vergara Wasserman (Brazilian Journal of Radiation Sciences, 2025)
Responding to incidents is part of the attributes of the agency whose mission is nuclear and radiological safety; in the Brazilian case, the National Nuclear Energy Commission (CNEN), an autonomous structure of the Ministry of Science, Technology and Innovation (MCTI). In 2022, the Nuclear and Radiological Emergency Response System (SAER) was activated to respond to a finding in a maritime container. The cargo, returned from abroad from a transshipment port, due to the detection of an internal radioactive source, arrived in the country at the Port of Suape, in Pernambuco; It is then analyzed by the CNEN technical team, following regulatory standards protocols. After work to remove the container of packed material – metal scrap – the radioactive source was located and identified, in the operation carried out in Caruaru-PE (headquarters of the holding company). Immediately, it was collected at the Regional Center for Nuclear Sciences - Northeast (CRCN-NE), in compliance with the country's safety regulations. Qualified and well-trained teams resulted in reliability of the process as a whole.